Field and laboratory characterization of corrosion potential in highway corrugated metal pipe - Crowder, Andrew Nicholas (Kansas State University, 2018)
Thousands of metallic drainage structures have been installed by the Kansas Department of Transportation (KDOT) to facilitate proper drainage of highway systems across the state. Several studies were conducted over the past 30 years by KDOT to determine the durability of different corrugated metal pipe (CMP) materials and estimate their performance against the deterioration that occurs due to the electrochemical process of corrosion. These past studies have influenced KDOT policy regarding pipe material, but a method to quickly determine the rate of deterioration, and accurately predict a service life, is still not well defined. With the last comprehensive study performed in 1990 by KDOT, there is now a need to perform a field evaluation to determine the performance of CMPs in Kansas. This research conducted a survey of observed CMP conditions for 80 sites across KDOT districts one and four using a quantitative observational rating system. The goal of the survey was to determine the performance of CMPs in the field. The findings of this study indicate that a 1975 change in KDOT pipe policy has increased the rapid deterioration of CMPs. An additional study was conducted to determine if accurate service life predictions could be made based on chemical and biological characteristics of soil taken near the CMP invert. A method to test the leachate water exposed to the soil sample was created. Laboratory results of four field samples indicated that the rate at which the invert deteriorated corresponded to the total amount of chloride anion mobilized in the leachate over a 72-hour period, along with the standard deviation of pH measured throughout the test. This contradicts most field corrosion tests that only measure field pH and resistivity. The developed method of measuring soil sample leachate may provide a more accurate estimate of the performance of CMP in the sample location.
Keywords: CMP; Underground corrosion; Corrugated metal pipe